10 Ways to Be a Better Interviewer. - MATSUDAIRA, KATE (Communications of the ACM, 2017)
The article offers advice on interviewing job candidates for software firm positions. Topics include the formulation of interview questions, the creation of an interview timeline, and the need for a positive attitude toward the interview. Also noted are the need to be collaborative during the interview, to engage in note-taking, and to offer real-world problems for the candidate to solve.